Abraham Maslow's Humanistic Approach In The Learning Of Mahārat al-Kitābah Class 7 Of Islamic Junior High School YMI Wonopringgo - Nurul Hidayah; Ahmad Taufiq (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2026)
This study aims to describe the implementation of Abraham Maslow’s humanistic approach in learning mahārah kitābah for seventh-grade students at SMP Islam YMI Wonopringgo. Writing skill is one of the complex competencies in Arabic language learning, involving cognitive, motor, and emotional aspects. This study employs a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The data analysis uses the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing. The results of the study indicate that the humanistic approach is implemented through the stages of planning, implementation, and evaluation of learning. The teacher fulfills students’ needs based on Maslow’s hierarchy, namely physiological needs, safety needs, love and belonging, esteem, and self-actualization. The learning process is carried out through cooperative learning, the use of visual media, ice breaking activities, and supportive evaluation. This approach has proven to improve students’ motivation, self-confidence, and writing skills in Arabic language learning.